Will Sparrow's Road - Cushman, Karen (New York : Clarion Books, 2012)
In 1599 England, twelve-year-old lying, thieving Will Sparrow runs away, meets many colorful characters on the road, and then reluctantly joins a traveling "oddities" exhibit, where he learns to see beyond appearances.
Includes bibliographical references (pp. 214-216).
Keywords: Conduct of life -- Fiction; Runaway children -- Fiction; Great Britain -- Fiction -- History -- 1485-1603, Tudors